BELORUSSIAN METALLURGICAL WORKS - STRATEGY OF SUCCESS - N. V. Andrianov (Литьë и металлургия, 2006)
It is shown that the problem of creation of highly skilled specialists at RUP '‘BM Z'' is being solved due to complex of measures integrated in system approach to progressive development of human resources of the plant. One of such measures is the project ''Gold ten”